Slurry for lithium ion battery positive electrode and manufacturing method therefor

The use of organic acids for pH adjustment in a water-based lithium-ion battery slurry, combined with a double oxide film coating, addresses the environmental and safety issues of inorganic acids, maintaining battery performance and reducing environmental impact.

JP2025015242AActive Publication Date: 2025-01-30HOUSEN KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023118528
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-30
Estimated Expiration
2043-07-20

AI Technical Summary

Technical Problem

Existing lithium-ion battery technologies face challenges in pH adjustment using inorganic acids, which are hazardous and environmentally unfriendly, leading to battery performance issues such as decreased capacity and lifespan due to lithium composite oxide deterioration when using water-based solvents.

Method used

A lithium-ion battery positive electrode slurry using organic acids for pH adjustment in a water-based solvent system, combined with a coating of lithium composite oxides and a double oxide film to prevent contact with water, ensuring safe and effective battery performance.

Benefits of technology

The solution provides a lithium-ion battery with reduced environmental impact, enhanced safety, and maintains battery performance comparable to organic solvent-based systems while avoiding the drawbacks of inorganic acids.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015242000002
    Figure 2025015242000002
  • Figure 2025015242000001
    Figure 2025015242000001
Patent Text Reader

Abstract

To provide slurry for a lithium ion battery positive electrode, giving a small load on an environment, having excellent safety and handleability, and being capable of providing a lithium ion battery showing battery performance equal to that of a lithium ion battery having a positive electrode formed from organic solvent-based electrode slurry.SOLUTION: Slurry for a lithium ion battery positive electrode includes positive electrode material, a binder, a solvent, and pH adjustment agent. The positive electrode material includes coated particles having lithium composite oxide particles and passive state films coating at least part ot their surfaces. The solvent includes water and the pH adjustment agent includes organic acid.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode for a lithium ion battery, and more particularly to a slurry for a positive electrode for a lithium ion battery, comprising a positive electrode material, a binder, a solvent and a pH adjuster. [Background technology]

[0002] In recent years, the rapid development of electric vehicles has led to a dramatic increase in the production of lithium-ion batteries, which are the core devices of electric vehicles. Lithium-ion batteries consist of a positive electrode, a negative electrode, an electrolyte, a separator, and peripheral components. The positive electrode is generally formed by mixing an oxide containing lithium ions as an active material, carbon as a conductive material, an appropriate amount of adhesive, and a solvent to form a slurry, which is then used as a coating liquid to coat a thin aluminum foil and dried.

[0003] For the adhesive, fluorine-based polymers such as polyvinylidene fluoride (PVDF) are used, taking into consideration their adhesion to the active material, their resistance to the polar solvent used as the electrolyte, and their stability in the electrochemical environment. For the solvent, an organic solvent capable of dissolving PVDF is used. The most common organic solvent is N-methylpyrrolidone (NMP).

[0004] In recent years, NMP has been pointed out as an environmental hormone and is therefore required to be collected after use. In response to this, water, which has a small environmental impact and is easy to treat, has been attracting attention as a solvent for the coating liquid.

[0005] However, the lithium composite oxide, which is the positive electrode active material, reacts with water and deteriorates, resulting in a problem of poor battery performance. In addition, the lithium composite oxide contains lithium hydroxide as an unreacted synthetic material, and its pH value increases when it comes into contact with water. In the case of a strongly alkaline slurry, the aluminum current collector corrodes during coating, resulting in a problem of reduced capacity and lifespan of the lithium ion battery.

[0006] Patent Document 1 describes that the positive electrode active material is neutralized with an aqueous sulfuric acid solution, and then the neutralization product is removed by washing with water to lower the pH of the positive electrode slurry and suppress the corrosion of the current collector. However, when an inorganic acid such as sulfuric acid is used as a neutralizing agent for the positive electrode slurry, there are problems in that the positive electrode active material may dissolve when added, and the pH lowering effect is strong, making it difficult to adjust the pH value to a desired level.

[0007] Patent Document 2 describes that by adding an organic acid to an organic solvent-based slurry for electrodes using a vinylidene fluoride-based binder and an NMP solvent, an increase in viscosity during coating is prevented and the vinylidene fluoride-based binder is prevented from swelling in the electrolyte of the formed electrode, thereby preventing a decrease in adhesive effect.

[0008] Patent Document 3 describes that by covering positive electrode active material particles with a transition metal oxide, even when a positive electrode is coated using a slurry made of an aqueous solvent, the positive electrode active material layer is prevented from coming into contact with water, the slurry does not exhibit strong alkalinity, and corrosion of the current collector and the like are prevented. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2009-230863 A [Patent Document 2] Japanese Patent Application Publication No. 9-180725 [Patent Document 3] International Publication No. 2012 / 111116 Summary of the Invention [Problem to be solved by the invention]

[0010] The method of lowering the pH of a positive electrode slurry in Patent Document 1 uses an inorganic acid as a pH adjuster that has a strong pH lowering effect, making it difficult to handle, less safe, and placing a large burden on the environment. On the other hand, organic acids are pH adjusters that exhibit a buffering effect and have a gradual pH lowering effect, making them easy to handle, highly safe, and placing a small burden on the environment.

[0011] However, in order to lower the pH value to a desired level using an organic acid in an aqueous positive electrode slurry that uses water as a solvent, a large amount of the organic acid must be added, and the organic acid and neutralized salt remain in the formed positive electrode, resulting in a problem of reduced battery performance of the lithium-ion battery, particularly the electrode energy density.

[0012] The present invention has been made to solve the above problems, and an object of the present invention is to provide a slurry for the positive electrode of a lithium ion battery, which has a small environmental impact, is excellent in safety and ease of handling, and can provide a lithium ion battery that exhibits battery performance equivalent to that of a lithium ion battery having a positive electrode formed from an organic solvent-based electrode slurry. [Means for solving the problem]

[0013] [Form 1] A slurry for a positive electrode of a lithium ion battery comprising a positive electrode material, a binder, a solvent and a pH adjuster, The positive electrode material includes coated particles having lithium composite oxide particles and a passivation film that coats at least a portion of the surface of the lithium composite oxide particles, The solvent comprises water; The slurry for a positive electrode of a lithium ion battery, wherein the pH adjuster contains an organic acid.

[0014] [Form 2] The slurry for a positive electrode of a lithium ion battery according to Form 1, wherein the solvent is substantially free of an organic solvent.

[0015] [Mode 3] The slurry for a positive electrode of a lithium ion battery according to Mode 1 or 2, wherein the pH adjuster is substantially free of inorganic acid.

[0016] [Form 4] A slurry for a positive electrode of a lithium ion battery according to any one of Forms 1 to 3, having an organic acid concentration of 2 to 8% by weight.

[0017] [Form 5] A slurry for a positive electrode of a lithium ion battery according to any one of Forms 1 to 4, having a pH of 6 to 9.

[0018] [Mode 6] The slurry for a positive electrode of a lithium ion battery according to any one of Modes 1 to 5, wherein the passive film has a coating amount of 1 to 20% by weight.

[0019] [Mode 7] A slurry for a positive electrode of a lithium ion battery according to any one of Modes 1 to 6, wherein the passive film contains aluminum oxide or magnesium oxide.

[0020] [Mode 8] The slurry for a positive electrode of a lithium ion battery according to any one of Modes 1 to 7, wherein the organic acid is at least one selected from the group consisting of acrylic acid, formic acid, citric acid, acetic acid, oxalic acid, lactic acid, pyruvic acid, malonic acid, propionic acid, maleic acid, and butyric acid.

[0021] [Mode 9] A slurry for a positive electrode of a lithium ion battery according to any one of Modes 1 to 8, wherein the positive electrode active material comprises Ni:Co:Mn in a weight ratio of about 8:1:1.

[0022] [Mode 10] A positive electrode for a lithium ion battery, comprising the slurry for a positive electrode for a lithium ion battery according to any one of Modes 1 to 9.

[0023] [Form 11] A lithium ion battery comprising the positive electrode of the lithium ion battery of Form 10.

[0024] [Form 12] A method for producing a slurry for a positive electrode of a lithium ion battery, comprising mixing a positive electrode material having a lithium composite oxide and a passivation coating covering at least a portion of the surface of the positive electrode material, water as a solvent, and an organic acid as a pH adjuster.

[0025] [Mode 13] A method for producing a positive electrode for a lithium ion battery, comprising forming a layer of the positive electrode slurry according to any one of Modes 1 to 9 on a current collector made of aluminum or an aluminum alloy, and drying the layer. Effect of the Invention

[0026] According to the present invention, a slurry for a positive electrode of a lithium ion battery is provided, which has a small environmental impact and is excellent in safety and ease of handling. By using the slurry for a positive electrode of a lithium ion battery of the present invention, a lithium ion battery exhibiting battery performance equivalent to that of a lithium ion battery having a positive electrode formed from an organic solvent-based electrode slurry can be provided. [Brief description of the drawings]

[0027] [Figure 1] 1 is an exploded view showing a schematic configuration of a lithium ion battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] The scope of the present invention is not limited to the embodiments described herein, and various modifications can be made without departing from the spirit of the present invention. In addition, when multiple upper and lower limit values ​​are described for a specific parameter, any upper and lower limit values ​​can be combined to form a suitable numerical range.

[0029] The positive electrode slurry of the lithium ion battery of the present invention contains a positive electrode material, a binder, an aqueous solvent, and a pH adjuster.

[0030] <Cathode materials> The positive electrode material is an electrode material containing a positive electrode active material. The active material means a material that directly contributes to electrode reactions such as charge reactions and discharge reactions. The positive electrode material used in the present invention contains coated particles having positive electrode active material particles and a passivation film that covers at least a part of the surface of the positive electrode active material particles. This suppresses contact between the positive electrode active material and the aqueous solvent, prevents deterioration of the positive electrode active material, and suppresses an increase in the pH of the slurry.

[0031] The type of the positive electrode active material is not particularly limited, but preferably, a lithium composite oxide is used. The lithium composite oxide refers to a composite oxide containing lithium and a transition metal (e.g., nickel, cobalt, manganese, etc.). The lithium composite oxide has low water resistance, and by suppressing contact with an aqueous solvent, a remarkable effect is achieved.

[0032] Specific examples of lithium composite oxides include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and ternary materials (LiNi 0.33 Co2Mn 0.33 O2), nickel-rich ternary materials (LiNi 0.5 Co 0.2 Mn 0.3 O2), high nickel ternary materials (LiNi 0.8 Co 0.1 Mn 0.1 O2), lithium nickel-cobalt-aluminum oxide (LiNi 0.8 Co 0.15 Al 0.05 O2), lithium iron phosphate (LiFePO4), lithium iron manganese phosphate (LiFe 0.5 Mn 0.5 PO4), lithium manganese phosphate (LiMnPO4), lithium cobalt phosphate (LiCoPO4), lithium nickel phosphate (LiNiPO4), lithium vanadium phosphate (Li3V2(PO4)3), lithium iron silicate (Li2FeSiO4), lithium manganese silicate (Li2MnSiO4), lithium-rich solid solution system (Li2MnO3-LiNi 0.33 Mn 0.33 Co 0.33 O2), lithium manganese spinel oxide (LiMn2O4), lithium nickel manganese spinel oxide (LiNi 0.5 Mn 1.5 O4), lithium nickel-iron-manganese oxide (LiNi 0.33 Fe 0.33 Mn 0.33O2), and the like, which may be used alone or in combination of two or more. Among them, preferred lithium composite oxides include high-nickel ternary materials and lithium iron phosphate.

[0033] The passive film that covers the positive electrode active material is a film made of an amphoteric oxide. An amphoteric oxide is a metal oxide that acts as either an acid or a base in a neutralization reaction to form a salt. Metals that constitute amphoteric oxides include copper, zinc, lead, tin, beryllium, and aluminum. Preferred amphoteric oxides include aluminum oxide, titanium oxide, and zinc oxide.

[0034] The passive film that covers the positive electrode active material can be formed, for example, as follows. First, a water-soluble compound of a metal that constitutes an amphoteric oxide is prepared and dissolved in water. The obtained coating liquid and particles of the positive electrode active material are mixed to coat the surfaces of the particles with the coating liquid. The wet-coated particles are dried and then fired to convert the wet coating on the particle surfaces into a metal oxide coating. Examples of the water-soluble compound of the metal include aluminum nitrate and aluminum phosphate.

[0035] The coating amount of the passive film can be adjusted by increasing or decreasing the metal compound concentration in the coating liquid or the mixing amount of the coating liquid. The coating amount of the passive film can be calculated by comparing the weight of the electrode active material particles before and after coating, according to the formula: Coating amount (wt%)={(coated particle weight-electrode active material particle weight) / coated particle weight}×100 (1) The amount is determined according to the following:

[0036] The coating amount of the passivation film on the positive electrode active material is preferably adjusted to 1 to 20% by weight. When the coating amount of the passivation film is less than 1% by weight, the degree of contact between the positive electrode active material and the aqueous solvent increases, and the positive electrode active material is likely to deteriorate. Also, the pH increase of the slurry becomes large, and a large amount of pH adjuster is required to lower the pH to a desired value, resulting in a decrease in battery performance. When the coating amount of the passivation film exceeds 10% by weight, the content of the positive electrode active material in the positive electrode material decreases, and the battery performance deteriorates. The coating amount of the passivation film is more preferably 2 to 8% by weight, and even more preferably 2 to 5% by weight.

[0037] <aqueous solvent> In this specification, the aqueous solvent refers to water or a solvent mainly composed of water. By using an aqueous solvent, the environmental load in the positive electrode manufacturing process can be reduced. From the viewpoints of cost and environmental load, it is preferable to use water alone as the aqueous solvent.

[0038] <binder> The binder is a material that binds the particles of the positive electrode material to each other and also binds the positive electrode material to the current collector. As the binder, water-soluble polymers and polymer fine particles that can be mixed and used in an aqueous solvent are used. Specific examples of the water-soluble polymer include carboxymethyl cellulose and polyacrylic acid. Specific examples of the polymer fine particles include nitrile rubber (NBR), styrene-butadiene rubber (SBR), polyacrylate, and the like.

[0039] <pH adjuster> The pH adjuster is a compound that can react with hydroxide ions to lower the pH of the positive electrode slurry. The pH adjuster is preferably one that is likely to scatter by decomposition or evaporation during the process of applying the slurry as a coating liquid to the current collector and drying, and is difficult to remain in the formed electrode, and is also preferably one that is difficult to react with the electrode active material.

[0040] The pH adjuster used in the present invention is an organic acid. This makes it easy to adjust the slurry to a desired pH value, is highly safe, and reduces the environmental impact in the positive electrode manufacturing process. Examples of organic acids that are preferably used include acrylic acid, formic acid, citric acid, acetic acid, oxalic acid, lactic acid, pyruvic acid, malonic acid, propionic acid, maleic acid, and butyric acid. Among these, preferred organic acids are acetic acid, oxalic acid, malonic acid, and maleic acid, and particularly preferred organic acid is acetic acid.

[0041] The amount of organic acid added is an amount that results in a concentration of 1 to 9% by weight in the slurry. If the amount of organic acid added is less than 2% by weight, the pH rise of the slurry is not sufficiently suppressed, and if it exceeds 8% by weight, the organic acid and neutralized salt remain in the molded positive electrode, which may deteriorate the battery performance of the lithium ion battery. The amount of organic acid added is preferably 2 to 8% by weight, more preferably 2 to 5% by weight.

[0042] The pH of the positive electrode slurry is preferably 6 to 9. If the pH of the positive electrode slurry is less than 6, the content of the pH adjuster is high, and organic acid and neutralized salt remain in the molded positive electrode, which may deteriorate the battery performance of the lithium ion battery. If the pH of the positive electrode slurry exceeds 9, corrosion and dissolution of the aluminum current collector surface are likely to occur during coating. The pH of the positive electrode slurry is more preferably 6 to 8, and further preferably 7 to 8.

[0043] <Positive electrode slurry> The positive electrode slurry of the present invention may contain, in addition to the positive electrode material, binder, aqueous solvent and pH adjuster, conventionally used components such as conductive materials and additives.

[0044] Examples of the conductive material include carbon black, graphite, carbon fiber, metal fiber, etc. Examples of the carbon black include acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, etc. The conductive material can be used alone or in combination of two or more.

[0045] To prepare the positive electrode slurry, a method commonly used in this field can be adopted. For example, a method of mixing the above-mentioned components using a mixing device such as a planetary mixer, a homomixer, a pin mixer, a kneader, or a homogenizer can be mentioned. The mixing device is used alone or in combination of two or more. Furthermore, various dispersants, surfactants, stabilizers, etc. may be added as necessary when kneading the positive electrode slurry.

[0046] <Positive electrode of lithium-ion battery> The positive electrode of the lithium ion battery can be manufactured by using the positive electrode slurry of the present invention and the same method as in the past. For example, the positive electrode slurry is applied to a current collector, dried to form a positive electrode mixture layer, and further rolled as necessary to obtain a positive electrode. The positive electrode mixture layer may be formed on both sides of the current collector in the thickness direction. The thickness of the positive electrode mixture layer is preferably 20 to 150 μm when formed on one side of the positive current collector, and is preferably 50 to 250 μm in total when formed on both sides of the current collector.

[0047] The current collector may be one commonly used in the field of lithium ion batteries, such as a sheet or foil containing stainless steel, aluminum, an aluminum alloy, or titanium. The sheet may be porous. Examples of the porous material include foam, woven fabric, and nonwoven fabric. The thickness of the sheet or foil is not particularly limited, but is usually 1 to 500 μm, preferably 8 to 60 μm. Among these, aluminum, an aluminum alloy, and the like are preferred. The surface of the current collector may be subjected to lath processing or etching.

[0048] The positive electrode slurry can be applied to the surface of the current collector using, for example, a slit die coater, a reverse roll coater, a lip coater, a blade coater, a knife coater, a gravure coater, a dip coater, etc. The positive electrode slurry applied to the current collector is preferably dried in a manner similar to natural drying, but in consideration of productivity, it is preferably dried at a temperature of 100° C. to 350° C. for 10 minutes to 1 hour.

[0049] The rolling may be performed several times using a roll press at a line pressure of 1000 to 6000 kg / cm until the positive electrode has a predetermined thickness of 130 μm to 200 μm, or the line pressure may be changed.

[0050] <Lithium-ion battery> The lithium ion battery of the present invention can have the same configuration as a conventional lithium ion battery, except that it uses a positive electrode prepared using the positive electrode slurry of the present invention.

[0051] Fig. 1 is an exploded view showing a schematic configuration of a lithium-ion battery according to one embodiment of the present invention. The lithium-ion battery shown in Fig. 1 is a coin-type lithium-ion battery, and is composed of an electrode plate assembly using the positive electrode 4, an electrolyte (not shown), and a battery case that contains these. The electrode plate assembly is composed of a sheet-shaped positive electrode 4, a sheet-shaped negative electrode 6, and a sheet-shaped separator 5 that provides insulation between the positive electrode 4 and the negative electrode 6.

[0052] These are stacked together with a leaf spring 2, a spacer 3, a gasket 7, etc., which are commonly used in the field of lithium ion batteries, and are housed in battery cases 1, 8.

[0053] The positive electrode 4 has the same structure as the positive electrode of the present invention described above. That is, the positive electrode 4 includes a current collector and a positive electrode mixture layer, and the positive electrode mixture layer is supported on the surface of the current collector and contains the positive electrode material. The positive electrode 4 is produced, for example, by applying a positive electrode slurry to both sides of the current collector, drying the slurry, and rolling the slurry to form a positive electrode mixture layer.

[0054] The negative electrode 6 is produced, for example, by applying a negative electrode slurry to one or both sides of a current collector, drying it, and rolling it to form a negative electrode mixture layer.

[0055] The negative electrode current collector may be one commonly used in the field of lithium ion batteries, and preferably has a thickness in the range of 10 μm to 50 μm. The surface of the current collector may be lathed or etched.

[0056] The negative electrode slurry is prepared by mixing the negative electrode active material, the binder, and the dispersion medium. If necessary, a conductive agent, a thickener, etc. may be added to the negative electrode slurry.

[0057] The negative electrode active material is not particularly limited, but it is preferable to use a carbon material that can absorb and release lithium ions by charging and discharging. For example, a carbon material obtained by burning an organic polymer compound (phenolic resin, polyacrylonitrile, cellulose, etc.), a carbon material obtained by burning coke or pitch, artificial graphite, natural graphite, pitch-based carbon fiber, PAN-based carbon fiber, etc. are preferable. The shape of the negative electrode active material can be fibrous, spherical, scaly, or lumpy.

[0058] The binder, conductive material, and dispersion medium may be any of those commonly used in this field. For example, the same binder, conductive material, and dispersion medium as those used in the positive electrode 4 may be used.

[0059] A microporous film made of a polymeric material is preferably used as the separator 5. Examples of the polymeric material include polyethylene, polypropylene, polyvinylidene fluoride, polyvinylidene chloride, polyacrylonitrile, polyacrylamide, polytetrafluoroethylene, polysulfone, polyethersulfone, polycarbonate, polyamide, polyimide, polyether (polyethylene oxide and polypropylene oxide), cellulose (carboxymethyl cellulose and hydroxypropyl cellulose), poly(meth)acrylic acid, and poly(meth)acrylic acid ester.

[0060] These polymer materials can be used alone or in combination of two or more. Also, a multi-layer film in which these microporous films are laminated can be used. Among them, microporous films made of polyethylene, polypropylene, polyvinylidene fluoride, etc. are preferable. The thickness of the microporous film is preferably 10 μm to 30 μm.

[0061] The battery case may be made of copper, nickel, stainless steel, nickel-plated steel, etc. Metal plates made of these materials may be formed into the shape of the battery case by drawing, etc. In order to increase the corrosion resistance of the battery case, the processed battery case may be plated.

[0062] Furthermore, by using a battery case made of aluminum or an aluminum alloy, a lightweight rectangular secondary battery with high energy density can be produced.

[0063] The non-aqueous solvent preferably contains a cyclic carbonate and a chain carbonate as main components. For example, the cyclic carbonate is preferably at least one selected from ethylene carbonate, propylene carbonate, and butylene carbonate. The chain carbonate is preferably at least one selected from the group consisting of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0064] As the solute, for example, a lithium salt whose anion has a functional group with strong electron-withdrawing properties is used. Examples of these include LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiN(SO2CF3)2, LiN(SO2C2F5)2, and LiC(SO2CF3)3. These solutes may be used alone or in combination of two or more. In addition, these solutes are preferably dissolved in the non-aqueous solvent at a concentration of 0.5 to 1.5M. EXAMPLES

[0065] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to these examples.

[0066] <Production Example 1> Preparation of coated positive electrode material 1 A high-nickel ternary material with an average particle size of 3 μm, a tap density of 2.5 g / cc, and a Ni:Co:Mn weight ratio of 8:1:1 was obtained from the market. This was designated as cathode material A. Cathode material A was uniformly mixed with a 25 w / v% aluminum nitrate aqueous solution, and the resulting dispersion was spray-dried. The dried particles were fired at 600° C. for 10 hours to form an aluminum oxide coating on the particle surface. The resulting coated particles were designated as coated cathode material 1.

[0067] In the coated positive electrode material 1, the coating amount of aluminum oxide was adjusted by adjusting the concentration of the coating solution. The coating amount of aluminum oxide was determined according to the above formula (1) by comparing the weights of the positive electrode material before and after coating.

[0068] <Production Example 2> Preparation of coated positive electrode material 2 Except for using a 15 w / v % aluminum nitrate-ethanol solution instead of the aluminum nitrate aqueous solution, coated particles were obtained in the same manner as in Production Example 1. The obtained coated particles are designated as coated positive electrode material 2.

[0069] <Production Example 3> Production of coated positive electrode material 3 A lithium iron phosphate (LiFePO4) cathode material with an average particle size of 3 μm and a tap density of 1.8 g / cc was obtained from the market. This is called cathode material B. Cathode material B was uniformly mixed with a 25 w / v% aluminum nitrate aqueous solution, and the resulting dispersion was spray-dried. The dried particles were baked at 600°C for 10 hours to form an aluminum oxide coating on the particle surface. The resulting coated particles are called coated cathode material 3.

[0070] <Examples and Comparative Examples> Electrodes coated from water-based slurry In the examples and comparative examples, the positive electrode materials used were the positive electrode materials A (Ni:Co:Mn weight ratio 8:1:1), B (lithium iron phosphate (LiFePO4)), and coated positive electrode materials 1, 2, and 3 obtained by coating these with aluminum oxide.

[0071] A dispersion of sodium carboxymethylcellulose (CMC-Na) and nitrile rubber (NBR) was prepared as a binder, and acetylene black (AB) was prepared as a conductive material. CMC-Na was dissolved in pure water to a concentration of 2% by weight. The positive electrode material and AB were dispersed in this solution, and the NBR dispersion was added. The pH was then adjusted by adding acetic acid. The weight ratio of the positive electrode material:AB:CMC:NBR in the obtained slurry was 95:2:1:2, and the solid concentration was 60 w / v%.

[0072] The slurry was applied to an aluminum foil using a doctor blade to a dry thickness of 100 μm, and then dried. A disk having a diameter of 13 mm was cut out from the resulting laminated foil to obtain a positive electrode.

[0073] A lithium metal anode with a thickness of 250 μm and a diameter of 14 mm, a 1.0MLiPF6 / (EC:DEC=4:6) electrolyte, a separator, a gasket, a case, and other commonly used parts were prepared, and a lithium ion battery cell was assembled using the obtained cathode. The ratio of the weight of the cathode to the anode was adjusted to 1:1.1. An exploded perspective view of the cell is shown in Figure 1.

[0074] Next, a charge / discharge test was performed on the cell under the following conditions using a charge / discharge tester, and the initial capacity and the capacity retention rate after 100 charge / discharge cycles were determined.

[0075] Current: 0.lmAh Mode: CCCVCC(0.05C cutoff)CC Temperature: 35℃ Positive voltage range: 3.0V~4.2V

[0076] The type of positive electrode, the amount of coating, the pH of the slurry, the initial capacity, and the capacity retention rate are shown in Table 1. The initial capacity is expressed as a relative value with the result obtained in the following Reference Example for the same type of positive electrode material taken as 100%. The capacity retention rate is expressed as a relative value with the initial capacity taken as 100%.

[0077] <Reference examples 1 and 2> Positive electrode coated from organic solvent-based slurry As the positive electrode material, in Reference Example 1, positive electrode material A (Ni:Co:Mn weight ratio 8:1:1) was used, and in Reference Example 2, positive electrode material B (lithium iron phosphate (LiFePO4)) was used.

[0078] Polyvinylidene fluoride (PVDF) was prepared as a binder, and N-methylpyrrolidone (NMP) was prepared as a solvent. The positive electrode material, a 12 wt% PVDF-NMP solution, and AB were mixed. The obtained slurry had a positive electrode material:AB:PVDF weight ratio of 95:2:3 and a solid content concentration of 60 w / v%.

[0079] A lithium ion battery cell was produced and tested in the same manner as in the example except for using this slurry. The cell using the positive electrode material A had an initial capacity of 180 mAh / g and a capacity retention rate after 100 charge / discharge cycles of 80%. The cell using the positive electrode material B had an initial capacity of 180 mAh / g and a capacity retention rate after 100 charge / discharge cycles of 88%.

[0080] [Table 1]

[0081] In the case of the aqueous slurry without pH adjustment, the pH rose to 13. As a result, the initial capacity of the cell fell to 26% of that of the reference example, and degradation progressed with increasing cycles. On the other hand, when the pH of the slurry was adjusted to about 7, the initial capacity of the cell improved significantly, exceeding 90% of that of the reference example, and in some cases it was equivalent.

[0082] Furthermore, when the surface of the positive electrode material was coated, the cell performance was significantly improved. With a coating amount of about 5%, the pH of the slurry could be suppressed to about 8 without using a pH adjuster. In this case, the initial capacity of the cell was equivalent to that of the reference example, and the capacity retention rate was better than that of the reference example. In addition, the effect was enhanced by using a pH adjuster in combination. For example, when the coating amount was about 1-5% and about 2-5% of a pH adjuster was added, the initial capacity was almost 100% compared to the reference example, and the capacity retention rate was also greatly improved. [Explanation of symbols]

[0083] 1, 8 cases 2. Leaf spring 3 Spacer 4 Positive electrode 5. Separator 6 negative electrode 7 Gasket

Claims

1. A slurry for a positive electrode of a lithium ion battery comprising a positive electrode material, a binder, a solvent and a pH adjuster, The positive electrode material includes coated particles having lithium composite oxide particles and a passivation film that coats at least a portion of the surface of the lithium composite oxide particles, The solvent comprises water; The slurry for a positive electrode of a lithium ion battery, wherein the pH adjuster contains an organic acid.

2. 2. The lithium ion battery positive electrode slurry according to claim 1, wherein the solvent is substantially free of an organic solvent.

3. 2. The slurry for a positive electrode of a lithium ion battery according to claim 1, wherein the pH adjuster is substantially free of inorganic acid.

4. The slurry for a positive electrode of a lithium ion battery according to claim 1, having an organic acid concentration of 2 to 8% by weight.

5. The slurry for a positive electrode of a lithium ion battery according to claim 1, having a pH of 6 to 9.

6. The slurry for a positive electrode of a lithium ion battery according to claim 1, wherein the passive film has a coating amount of 1 to 20% by weight.

7. 2. The slurry for a positive electrode of a lithium ion battery according to claim 1, wherein the passivation film comprises aluminum oxide or magnesium oxide.

8. 2. The slurry for a positive electrode of a lithium ion battery according to claim 1, wherein the organic acid is at least one selected from the group consisting of acrylic acid, formic acid, citric acid, acetic acid, oxalic acid, lactic acid, pyruvic acid, malonic acid, propionic acid, maleic acid, and butyric acid.

9. 2. The lithium ion battery cathode slurry of claim 1, wherein the cathode active material comprises Ni:Co:Mn in a weight ratio of about 8:1:

1.

10. A positive electrode for a lithium ion battery, comprising the slurry for a positive electrode for a lithium ion battery according to claim 1.

11. A lithium ion battery comprising the positive electrode of the lithium ion battery according to claim 10.

12. A method for producing a slurry for a positive electrode of a lithium ion battery, comprising mixing a positive electrode material having a lithium composite oxide and a passivation coating covering at least a portion of the surface of the positive electrode material, water as a solvent, and an organic acid as a pH adjuster.

13. A method for producing a positive electrode for a lithium ion battery, comprising forming a layer of the positive electrode slurry according to claim 1 on a current collector made of aluminum or an aluminum alloy, and drying the layer.

Citation Information

Patent Citations

  • Positive electrode material for lithium secondary battery

    JP2006164758A

  • Manufacturing method for positive electrode for nonaqueous electrolyte battery, slurry used for the method, and nonaqueous electrolyte battery

    JP2009064564A

  • Composite particle for electrochemical device positive electrode, electrochemical device, and method for manufacturing composite particle for electrochemical device positive electrode

    JP2014132559A

  • Slurry for positive electrode of lithium ion secondary cell, positive electrode obtained using said slurry, method for manufacturing said positive electrode, lithium ion secondary cell formed using said positive electrode, and method for manufacturing said cell

    WO2015146649A1

  • Binder solution for battery and electrode mix

    JP1997180725A